POTENSI NASKAH KUNO DI KALIMANTAN BARAT : STUDI AWAL MANUSKRIP KOLEKSI H. ABDURRAHMAN HUSIN FALLUGAH AL-MAGHFURLAHU DI KOTA PONTIANAK - Faizal Amin (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
At certain level, this writing is a field research. The primary sources isthe ancient manuscript, the collection of H. Abdurrahman Husin Fallugah al-Maghfurlahu at Pontianak city. Some codicological aspects are used, inparticular in the case of making inventory and manuscript description. Thiswriting elaborates three parts of study. The first, concerning the identifications ofthe places in which the manuscripts reserved. The second, concerning thedescription of the manuscript in Pontianak city, in particular the collections of H.Abdurrahman Husin Fallugah al-Maghfurlahu. The third is concerning theidentification of same codicological aspects of the manuscripts.